2008
DOI: 10.1007/s11103-007-9280-6
|View full text |Cite
|
Sign up to set email alerts
|

CYP82E4-mediated nicotine to nornicotine conversion in tobacco is regulated by a senescence-specific signaling pathway

Abstract: Nicotine to nornicotine conversion in tobacco (Nicotiana tabacum L.) is regulated by an unstable converter locus which in its activated state gives rise to a high nornicotine, low nicotine phenotype in the senescing leaves. In plants that carry the high nornicotine trait, nicotine conversion is primarily catalyzed by a cytochrome P450 protein, designated CYP82E4 whose transcription is strongly upregulated during leaf senescence. To further investigate the regulation of CYP82E4 expression, we examined the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 51 publications
(51 reference statements)
0
22
1
Order By: Relevance
“…It has been reported that CYP82E4 is expressed at very low levels in green healthy leaves and is strongly induced during senescence (Siminszky et al, 2005;Gavilano et al, 2006;Chakrabarti et al, 2008). Therefore, we investigated whether the increased CYP82E4 expression could have been triggered by leaf senescence.…”
Section: Ntmthfr1 Negatively Affects Cyp82e4 Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that CYP82E4 is expressed at very low levels in green healthy leaves and is strongly induced during senescence (Siminszky et al, 2005;Gavilano et al, 2006;Chakrabarti et al, 2008). Therefore, we investigated whether the increased CYP82E4 expression could have been triggered by leaf senescence.…”
Section: Ntmthfr1 Negatively Affects Cyp82e4 Expressionmentioning
confidence: 97%
“…The synthesized nicotine is translocated through the xylem and transported to the leaves (Morita et al, 2009;Shoji et al, 2009;Hildreth et al, 2011), where it accumulates. In the leaf, nicotine can undergo N-demethylation to produce nornicotine (Griffith et al, 1955;Chakrabarti et al, 2008). Nornicotine is the second most abundant alkaloid in most tobacco cultivars (Saitoh et al, 1985), and its conversion is mainly controlled by the nicotine N-demethylase gene CYP82E4 (Siminszky et al, 2005;Xu et al, 2007).…”
mentioning
confidence: 99%
“…Nornicotine is accumulated to high levels in some tobacco (Nicotiana tabacum) cultivars and many wild Nicotiana species (Chakrabarti et al, 2008, Chelvarajan et al, 1993, Pakdeechanuan et al, 2012, Siminszky et al, 2005.…”
Section: Cytochrome P450s In Alkaloid Biosynthesismentioning
confidence: 99%
“…Investigations conducted on conversion locus analysis in Nicotiana spp. are limited to the varieties of the important commercial tobacco, mainly N. tabacum (Cai et al, 2012a, Siminszky et al, 2005, Chakrabarti et al, 2008, Gavilano et al, 2006, Lewis et al, 2010) and its progenitor species N. tomentosiformis (Mann et al, 1964), and N. sylvestris (Chakrabarti et al, 2007). There is also a report of the loci and their functionality in a few South American wild species including N. langsdorffii and N. alata (Pakdeechanuan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation